2011
DOI: 10.1007/s11912-011-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

Variant Forms of Bladder Cancer: Basic Considerations on Treatment Approaches

Abstract: Variant forms of bladder cancer are non-urothelial neoplasms or urothelial carcinomas mixed with other histologies. Compared to pure urothelial carcinoma, they all present with a high stage and grade. Prognosis is variable and there is a lack of evidence regarding the ideal treatment approach, because of their relative infrequency and the noninclusion in bladder cancer randomized trials. Despite this, basic recommendations can be extracted from case series. In the present report, existent literature about vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 44 publications
1
39
0
2
Order By: Relevance
“…6 -8 Thus, it was suggested that perioperative chemotherapy might improve outcomes. 5,7 On subgroup analysis of patients who received adjuvant chemotherapy we found no difference in oncological outcomes between those with pure UTUC and variant UTUC histology. Scosyrev et al reported improved survival in 295 patients with squamous or glandular histological UCB variants after neoadjuvant chemotherapy and radical cystectomy compared to those with cystectomy alone.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…6 -8 Thus, it was suggested that perioperative chemotherapy might improve outcomes. 5,7 On subgroup analysis of patients who received adjuvant chemotherapy we found no difference in oncological outcomes between those with pure UTUC and variant UTUC histology. Scosyrev et al reported improved survival in 295 patients with squamous or glandular histological UCB variants after neoadjuvant chemotherapy and radical cystectomy compared to those with cystectomy alone.…”
Section: Discussionmentioning
confidence: 81%
“…3,4 Of patients with UCB those who harbor histological UC variants have features of more aggressive disease, such as more advanced disease and inferior survival, than patients with pure UC. [5][6][7][8] However, we cannot indiscriminately extrapolate findings from UCB to UTUC. 9 While a few studies and case series show the clinical and survival outcomes of patients with variant histology UTUC, conclusions are limited by small sample sizes and types of analyses.…”
Section: Purposementioning
confidence: 99%
“…All other characteristics, including those classified as 'treatment-altering were similar, indicating that our internal pathologists do not differ in their overall distribution of diagnoses from the general community. This implies that the observed discrepancies in the original and the repeat review internal pathology reports are more likely to be a result of the act of repeat review itself and not institution specific [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the past 2 decades, several studies have repeatedly shown the benefits of repeat review [7][8][9][10][11][12]. Discrepancy rates between original and repeat histopathologic diagnosis have been studied widely in a variety of pathologies, with rates ranging from 10 to 30%.…”
Section: Discussionmentioning
confidence: 99%
“…2,14,[43][44][45] With regard to located SaC, a single therapeutic strategy is not described, so multimodal treatment is the most commonly used approach. 7,[46][47][48][49][50][51][52][53][54] surgery (cistectomy vs. TURB) in 95.2% of the cases, or surgery followed by external radiotherapy. A subgroup analysis was not performed between patients receiving surgery alone or those receiving surgery and radiotherapy.…”
Section: Treatmentmentioning
confidence: 99%